CLIMATE CHANGE, AGRICULTURE, AND LOCAL WISDOM - Hariadi, Untoro (Fakultas Pertanian, Universitas Janabadra, 2022)
This simple study attempts to see the link between climate change, agriculture, and local wisdom. With a descriptive-analytic method that relies on literature, this study wanted to show the need for fundamental changes to return to a